2023
DOI: 10.1038/s41598-023-33587-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation on the effect of insect-based chitosan on preservation of coated fresh cherry tomatoes

Abstract: Chitosan was produced from Hermetia illucens pupal exuviae by heterogeneous and homogeneous deacetylation. Tomato fruits (Solanum lycopersicum), that are one of the most grown and consumed food throughout the world, were coated with 0.5 and 1% chitosan, applied by dipping or spraying, and stored at room temperature or 4 °C, for a storage period of 30 days. Statistical analysis give different results depending on the analysed parameters: heterogeneous chitosan, indeed, had a better effect than the homogenous on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Chu et al found that both DPPH radical scavenging and ferric-chelating assays showed a positive correlation with the deacetylation degree of chitosan isolated from superworm (Zophobas morio) larvae [39]. Tafi et al reported that chitosan from Hermetia illucens as a coating for the preservation of a fresh food product was generally able to increase the phenolic and flavonoid content and the antioxidant activity of tomatoes during both RT and cold storage [144].…”
Section: Antioxidant and Anti-agng Activitymentioning
confidence: 99%
“…Chu et al found that both DPPH radical scavenging and ferric-chelating assays showed a positive correlation with the deacetylation degree of chitosan isolated from superworm (Zophobas morio) larvae [39]. Tafi et al reported that chitosan from Hermetia illucens as a coating for the preservation of a fresh food product was generally able to increase the phenolic and flavonoid content and the antioxidant activity of tomatoes during both RT and cold storage [144].…”
Section: Antioxidant and Anti-agng Activitymentioning
confidence: 99%
“…Coating solutions were prepared according to the method by Hassan et al and Tafi et al [8,57]. Chitosan (0.5% w/v or 1% w/v) was dissolved in a solvent solution consisting of 1% v/v acetic acid, 2% v/v glycerol and 0.2% v/v Tween-80.…”
Section: Preparation and Application Of Coating Solutionsmentioning
confidence: 99%
“…Fruits were coated by spraying using an aerograph (Martellato s.r.l., Rovigo, Italy) and then dried at room temperature for 30 min. The spraying with the coating solution was repeated twice to ensure uniform surface coverage, as reported by Tafi et al [57]. One half of the fruit of each treatment was stored at room temperature (RT), while the other half was stored at refrigeration temperature (4 °C).…”
Section: Preparation and Application Of Coating Solutionsmentioning
confidence: 99%
“…The inherent antibacterial quality of these films plays a pivotal role in mitigating bacterial growth within food products, consequently extending their shelf life and upholding the standard of food quality. As a consequence, these films are frequently harnessed in the context of food packaging, underlining their significance in bolstering food safety and minimizing waste [ 89 , 90 , 144 , 145 , 146 , 147 , 148 , 149 ].…”
Section: The Most Important Chitosan-based Antibacterial Materialsmentioning
confidence: 99%